Novel bio-based polymer membranes fabricated from isosorbide-incorporated poly(arylene ether)s for water treatment. (5th August 2020) - Kim, Dahee; Kim, In-Chul; Kwon, Young-Nam; Myung, Suwan
Graphical abstract: Highlights: Isosorbide-based PAES and PAEK were used to fabricate membranes for ultrafiltration. I-PAES and I-PAEK membranes exhibited higher hydrophilicity than PES membrane. PAES and I-PAEK membranes showed good antifouling properties. Abstract: Development of bio-based polymers for high-performance applications using isosorbide as renewable feedstock has garnered considerable research attention. Isosorbide, a bio-derived compound, is known to enhance the mechanical, thermal, and optical properties of a host polymer due to its unique molecular structure. In this study, two types of novel membrane polymer, isosorbide-based poly(arylene ether sulfone) (I-PAES) and poly(arylene ether ketone) (I-PAEK) were used to develop ultrafiltration membranes by the phase inversion technique. The physicochemical properties and filtration performance of the isosorbide-based membranes were investigated. I-PAES and I-PAEK membranes exhibited contact angles of 62.2° and 63.5°, respectively, which are lower than that of the polyethersulfone (PES) membrane (68.4°). The I-PAES and I-PAEK membranes showed lower flux decline ratios than PES membrane at the pHs examined in this study. Furthermore, the flux recovery ratios of the two bio-based membranes in cross-flow filtration experiments of a protein solution at pH 4 were about 16% and 17% higher than that of PES, respectively. At pH 9.5, the I-PAEK membrane exhibited an 11% higher flux recovery than the PES membrane. Ultrafiltration experiments with BSA revealed that the I-PAES and I-PAEK membranes are advantageous in terms of membrane fouling due to their high hydrophilicities; hence, they are possible replacements for PES membranes derived from petrochemicals.